Antifungal and Anti-Biofilm Activity of Essential Oil Active Components against Cryptococcus neoformans and Cryptococcus laurentii - Kumari, Poonam; Mishra, Rutusmita; Arora, Neha; Chatrath, Apurva; Gangwar, Rashmi; Roy, Partha; Prasad, Ramasare (Frontiers in Microbiology, 2017)
Cryptococcosis is an emerging and recalcitrant systemic infection occurring in immunocompromised patients. This invasive fungal infection is difficult to treat due to the ability of Cryptococcus neoformans and Cryptococcus laurentii to form biofilms resistant to standard antifungal treatment. The toxicity concern of these drugs has stimulated the search for natural therapeutic alternatives. Essential oil and their active components (EO-ACs) have shown to possess the variety of biological and pharmacological properties. In the present investigation the effect of six (EO-ACs) sourced from Oregano oil (Carvacrol), Cinnamon oil (Cinnamaldehyde), Lemongrass oil (Citral), Clove oil (Eugenol), Peppermint oil (Menthol) and Thyme oil (thymol) against three infectious forms; planktonic cells, biofilm formation and preformed biofilm of C. neoformans and C. laurentii were evaluated as compared to standard drugs. Data showed that antibiofilm activity of the tested EO-ACs were in the order: thymol>carvacrol>citral>eugenol=cinnamaldehyde>menthol respectively. The three most potent EO-ACs, thymol, carvacrol, and citral showed excellent antibiofilm activity at a much lower concentration against C. laurentii in comparison to C. neoformans indicating the resistant nature of the latter. Effect of the potent EO-ACs on the biofilm morphology was visualized using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM), which revealed the absence of extracellular polymeric matrix (EPM), reduction in cellular density and alteration in the surface morphology of biofilm cells. Further, to realize the efficacy of the EO-ACs in terms of human safety, cytotoxicity assays and co-culture model were evaluated. Thymol and carvacrol as compared to citral were the most efficient in terms of human safety in keratinocyte- Cryptococcus sp. co-culture infection model suggesting that these two can be further exploited as cost-effective and non-toxic anti-cryptococcal drugs. Keywords Cryptococcus neoformans, Cryptococcus laurentii, Biofilm, EO-ACs, SEM, CLSM